Minimum congestion routing for a 17 GHz wireless ad hoc network - Kotze, Daniel Johannes Van Wyk (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.